Hydrogen-air Combustion Limits at Low and Cryogenic Temperatures - Igor A. Kirillov; Vadim Yu. Plaksin (Chemical Engineering Transactions)
The effective advancement and societal acceptance of new LH2 systems and technologies depend on a comprehensive understanding of their safety levels. Beyond the general safety principles associated with LH2 solutions, it is essential to have detailed knowledge of their safety attributes, including concentration, pressure, and temperature limits. While well-established data exists for hydrogen-air combustion concentration limits at standard and elevated temperatures, there is a notable lack of information regarding these limits at low and cryogenic temperatures. This report aims to provide an exhaustive review of two categories of hydrogen-air combustion limits: concentration and temperature. It first highlights the existing gaps and deficiencies in the available empirical concentration limits for temperatures ranging from 90 K to 850 K. Following this, it introduces fundamental limits for detonation flames, deflagration flames, and flame balls, which are consistent regardless of the testing facility, methodology, or measurement standards. These fundamental limits help clarify some previously recorded experimental findings and shed light on the relationship between empirical and theoretical concentration limits. Additionally, the report makes a qualitative prediction of a newly identified combustion phenomenon referred to by the authors as the "cryogenic temperature limit for hydrogen combustion." Lastly, it offers practical suggestions for conservatively estimating the concentration limits of flames that could trigger fast turbulent or detonating flames at low and cryogenic temperatures, presented through an analytical correlation.